A Novel Accounting Knowledge Sharing System: A Conceptual Framework - Ayodele, Freida Ozavize; Liu, Yao; Hasnah, Haron (Tamkang University, Taiwan, 2017)
The factors which facilitate knowledge sharing in accounting functions as exchange systems are currently not well grasped in literature. This study aimed to identify and integrate these factors to develop a novel holistic accounting knowledge sharing (AKS) conceptual framework to guide empirical testing of knowledge sharing in the accounting unit of a university. The methodological approach employed is grounded on the integration of past empirical findings, theories, and interpretation of the authors. The outcome of the study revealed that identified accounting knowledge sharing enablers (AKSE) and accounting knowledge sharing processes (AKSP) as factors might have combined effect on the accounting knowledge sharing outcome (AKSO). Besides, prioritizing common task drive, which may be financially or non-financially inclined above other task drives (TD) can encourage knowledge sharing in accounting context. This study is significant as it informs managers and provides direction